No one ever told us that : money and life lessons for young adults - Spooner, John D. (Online access with DDA: Askews (Economics), 2015)
The 'new grownup' guide to managing your life and money in the modern economy, 'No One Ever Told Us That' is a series of essential life and financial lessons that every adult needs to read before they embark upon their own life's adventures.